Assessment of design mechanical parameters and partial safety factors for Wire-and-Arc Additive Manufactured stainless steel. (15th December 2020) - Laghi, Vittoria; Palermo, Michele; Gasparini, Giada; Veljkovic, Milan; Trombetti, Tomaso
Highlights: The calibration of design values of WAAM stainless steel is presented. The experimental results present high anisotropy related to the printing process. Yielding and ultimate tensile strength values are calibrated along three directions. Best-fit distributions and Eurocode 0 procedure are used for calibration of samples. Considerations on the high variability and anisotropy of Young's modulus are added. Abstract: Early investigations suggest that the use of Additive Manufacturing (AM) technologies for construction has the potential to decrease labor costs, reduce material waste, and create customized complex geometries that are difficult to be manufactured using conventional construction techniques. Nevertheless, the full exploitation of AM technologies requires data on the material mechanical properties so that reliable and safety design requirements can be developed. Among different metal AM techniques, the so-called Wire-and-Arc Additive Manufacturing (WAAM) results to be potentially suitable to realize large-scale structural elements of any shape and size. However, the results of early experimental tests on WAAM-produced alloys suggest the need of ad-hoc considerations to properly interpret the geometrical and mechanical features of the printed outcomes. The present study analyzes the data obtained from the experimental results of tensile tests carried out on WAAM-produced 308LSi stainless steel elements with the purpose of calibrating design values and partial safety factors. In order to account for the anisotropic behavior proper of WAAM-produced elements, the design values of the main mechanical parameters have been calibrated for the three main orientations of the specimens with respect to the deposition layer. The calibrated design values and partial safety factors for the yielding and ultimate tensile strength are compared with recommended values for stainless steel structures as provided by EN1993:1-4 - Eurocode 3 (EC3). Additional considerations upon the Young's modulus values, highly influenced by the anisotropic behavior of WAAM-produced stainless steel, are presented as well.